A 3‐D bonding perspective of the factors influencing the relative stability of the S1/S0 conical intersections of the penta‐2, 4‐dieniminium cation (PSB3). Issue 11 (14th January 2019) - Bin, Xin; Momen, Roya; Xu, Tianlv; Kirk, Steven R.; Filatov, Michael; Jenkins, Samantha
Abstract: A balanced treatment of the covalent and ionic contributions to the ground and excited states originating from torsion about double bonds is known to be strongly dependent on the presence of dynamic electron correlation. We undertake an analysis of the minimum energy pathways corresponding to deactivation of the first excited singlet state of PSB3. In doing so we consider torsion about the three double bonds including other intramolecular degrees of freedom, such as the bond length alternation. The 3‐D bond‐path analysis provides a new 'bond‐localized orbital‐like' directional interpretation of bonding. Therefore, we present a more sophisticated method of determination of the degree of covalent and ionic contributions known to be responsible for altering the relative stability of the S1 /S0 conical intersections. The results presented suggest that the commonly used simplified multi‐reference methodologies that often result in incorrect predictions for the excited state deactivation reaction mechanism. Abstract : The bond‐path framework set B visualization of the spectrum of the chemical character (covalent–biradical‐ionic) displayed of each of the back‐bone bonds as well as the influence on neighboring bonds. The most preferred directions of accumulation of charge density, q ‐ and q ′‐paths along the backbone bond‐path ( r ) corresponding to the torsional C10‐N12 BCP for the S0 (top) and S1 (below) states at a value of the torsion q = 90.0°.